2009
DOI: 10.1007/s11258-009-9596-1
|View full text |Cite
|
Sign up to set email alerts
|

Population ecology of yew (Taxus baccata L.) in the Central Apennines: spatial patterns and their relevance for conservation strategies

Abstract: Understanding the ecological mechanisms that allow a species to transition from an occasional understory component to the dominant type in the forest canopy is essential for predicting future shifts in the distribution of species. We investigated this issue with regard to yew, also because mature yew trees have been reported to inhibit self-regeneration and seedling survival, prompting concerns for the long-term preservation of the species. Our objectives were (a) to quantify spatial patterns of yew (Taxus bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 52 publications
9
56
1
Order By: Relevance
“…Dhar et al, 2007;Piovesan et al, 2009) but where should the priorities lie? The exact order of priority will, of course vary depending upon geographical location and dominant environmental stressors, and upon local management objectives, but we offer the following recommendations in approximate order of effectiveness weighed against cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dhar et al, 2007;Piovesan et al, 2009) but where should the priorities lie? The exact order of priority will, of course vary depending upon geographical location and dominant environmental stressors, and upon local management objectives, but we offer the following recommendations in approximate order of effectiveness weighed against cost.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, yew populations should have an area of at least 0.5-3.0 ha to be self-perpetuating (Piovesan et al, 2009) together with a minimum number of 40 individuals with more or less equal proportions of males and females (Iszkuło et al, 2009). Irrigation of seedlings in dry seasons is also crucial to their survival.…”
Section: Discussionmentioning
confidence: 99%
“…Negative allelopathic effects of yew and fir on the germination and growth of seedlings have been demonstrated in several studies (Del Moral and Cates 1971;Pelliser and Souto 1999;Thomas and Polwart 2003;Piovesan et al 2009). However, the allelopathic effects of yew saplings were not evident with the coexistence of fir seedlings.…”
Section: Discussionmentioning
confidence: 94%
“…It is often the result of larger or smaller natural gaps in the canopy of the stand (Leemans 1991). Geostatistical analysis in the Central Apennines found that yew occurred in patches and high density of mature yews suppressed regeneration (Piovesan et al 2009). The presence of gaps leads to a change in ecological conditions under the canopy.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, habitat fragmentation which is a typical consequence of human activities negatively impacts yew pollination and fitness because formation of viable seeds requires that individuals of both sexes co-exist on the landscape (yew is a dioeceous species). Land use changes are also likely to have contributed to shrinking yew habitat, through logging of oldgrowth stands, often in combination with grazing and burning [27]. Such activities have transformed the forest landscape and affected vegetation dynamics, especially of shade-tolerant and late-successional species such as yew [28,29].…”
Section: Discussionmentioning
confidence: 99%